2020
DOI: 10.3906/kim-2006-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite nanoparticles−based hydroxyl radical scavenging activity assay of antioxidants using N, N-dimethyl-p-phenylenediamine probe

Abstract: Excessive amounts of reactive oxygen species (ROS), unless counterbalanced by antioxidants, can cause cellular damage under oxidative stress conditions; therefore, antioxidative defenses against ROS must be measured. With the development of nanotechnology, nanoparticles have found numerous applications in science, health, and industries. Magnetite nanoparticles (Fe3O4:MNPs) have attracted attention because of their peroxidase-like activity. In this study, hydroxyl radicals (•OH) generated by MNPs-catalyzed deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Recently, the development of biocompatible nanoparticles that have antioxidant properties has attracted a great deal of attention [10]. In addition, magnetite nanoparticles possess an intrinsic enzyme mimetic activity similar to natural peroxidase activity [11]. The peroxidase-like activity of magnetite nanoparticles is based on the coexistence of Fe 2+ /Fe 3+ ion pairing in the structure, such as Fenton's reagent, which are known to catalyze the breakdown of hydrogen peroxide [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of biocompatible nanoparticles that have antioxidant properties has attracted a great deal of attention [10]. In addition, magnetite nanoparticles possess an intrinsic enzyme mimetic activity similar to natural peroxidase activity [11]. The peroxidase-like activity of magnetite nanoparticles is based on the coexistence of Fe 2+ /Fe 3+ ion pairing in the structure, such as Fenton's reagent, which are known to catalyze the breakdown of hydrogen peroxide [12].…”
Section: Introductionmentioning
confidence: 99%
“…They use N,N-dimethyl- p -phenylenediamine (DMPD) probe (°OH detector) and F3O4 NPs with the size of 20–30 nm. They showed that in concentration around 0.1 mg/ml, absorbance of solution (F3O4 NP + DMPD) was around 0.6 [ 72 ]. While we sense among of °OH with Terephthalic acid + Core: citric acid: PEG: ICG: PpIX MNPs in presence of magnetic field and achieve high amount of °OH production in with combination of MNPs and magnetic field.…”
Section: Discussionmentioning
confidence: 99%